2007
DOI: 10.4049/jimmunol.178.8.5271
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Hydroxide Adjuvants Activate Caspase-1 and Induce IL-1β and IL-18 Release

Abstract: Aluminum hydroxide (Alum) is the only adjuvant approved for routine use in humans, although the basis for its adjuvanticity remains poorly understood. In this study, we show that Alum activates caspase-1 and induce secretion of mature IL-1β and IL-18. Human PBMC or dendritic cells stimulated with pure TLR4 and TLR2 agonists released only traces of IL-1β or IL-18, despite the fact that the IL-1β mRNA was readily induced by both TLR agonists. In contrast, cells costimulated with TLR agonists plus Alum released l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
238
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(258 citation statements)
references
References 28 publications
13
238
1
3
Order By: Relevance
“…Thus, not surprisingly two authors reported a failure in IL-1b secretion in response to aluminium/alum powder resuspended in physiological buffer [10,12]. Therefore, although it has been shown that Imject s Alum is able to activate caspase-1 in vitro as much as licensed aluminium adjuvants do [10], the in vivo effects of a formulation with different physico-chemical parameters are unpredictable and could partially account for the differences observed in the above-mentioned studies [13,14,16,17].…”
Section: The Role Of Nlrp3 In Alum Immunostimulation Is Controversialmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, not surprisingly two authors reported a failure in IL-1b secretion in response to aluminium/alum powder resuspended in physiological buffer [10,12]. Therefore, although it has been shown that Imject s Alum is able to activate caspase-1 in vitro as much as licensed aluminium adjuvants do [10], the in vivo effects of a formulation with different physico-chemical parameters are unpredictable and could partially account for the differences observed in the above-mentioned studies [13,14,16,17].…”
Section: The Role Of Nlrp3 In Alum Immunostimulation Is Controversialmentioning
confidence: 95%
“…Another issue is the physico-chemical form of alum, which could be critical [10,20]. Some experiments [14,17] were performed with Imject s Alum, a proprietary formulation available for research purposes, which is a 1:1 mixture of aluminium hydroxide and magnesium hydroxide that differs considerably from the alum adjuvants licensed for human use.…”
Section: The Role Of Nlrp3 In Alum Immunostimulation Is Controversialmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that alum synergizes with TLR agonists in vitro to stimulate IL-1b production from human PBMC [18]. The paper by Franchi and Nfflaeez in this issue of the European Journal of Immunology [19] and the recent paper by Eisenbarth et al [20] have clarified the molecular mechanism of alum and TLR agonist cross-talk in mouse macrophages.…”
Section: Alum Activates Nlrp3 Inflammasome: Synergy With Tlr Agonistsmentioning
confidence: 98%
“…Recent studies have also shown that the commonly used adjuvant alum induced the release of IL-1␤, IL-18, and IL-33 52,53 that is mediated by NALP3. 54 Hence, to check whether adjuvancy of PNiPAAm also involves the inflammasome pathway, we analyzed IL-1␤ levels in the sera from PNiPAAm-CII-immunized mice and compared it with CII emulsified with Freund's adjuvant(s).…”
Section: Discussionmentioning
confidence: 99%